Sosialisasi Nilai Karakter dan Implementasinya pada Peserta Didik di SMA Pasundan 2 Kota Cimahi - Irawan, Ade; Riadi, Farid; Arifin, Yusuf; Kurniawan, Wawan (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2024)
Character education is an effort to develop a human child's character, character, morals, or ethics to live better, more humane, and more humane.   Given the importance of character education in community social interaction, it is therefore necessary to cultivate character education from an early age.Character education in the school environment is not only limited to understanding and understanding what character is, but needs to be implemented through daily actions by providing training and providing concrete examples to students.The implementation that is meant in the formation of character for Pasundan 2 Cimahi Senior High School students, is how Pasundan 2 Cimahi Senior High School students can behave in daily life in a school environment that reflects the character of Sundanese values as one of the goals in the form of the Pasundan Educational Institution is an Educational Institution that has inherent Sundanese characteristics, namely the Tri Identity Pengkuh Agamana (Nyantri-Silih Asih), Luhung Elmuna (Nyakola-Silih Asah), and Jembar Budayana (Nyunda-Silih Asuh), with these values, all activities, both academic and non-academic, are directed to the achievement of these values. The concept of the Tri Identity refers to three main aspects that are intended to be instilled in the formation of student character in the environment of the Higher and Secondary Education Foundation. Pengkuh Agamana (Nyantri-Silih Asih) in this aspect emphasizes the importance of religious values and spirituality in students' lives.